2018
DOI: 10.1146/annurev-chembioeng-060817-083953
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Engineering for Catalysis

Abstract: Crystal engineering relies upon the ability to predictively control intermolecular interactions during the assembly of crystalline materials in a manner that leads to a desired (and predetermined) set of properties. Economics, scalability, and ease of design must be leveraged with techniques that manipulate the thermodynamics and kinetics of crystal nucleation and growth. It is often challenging to exact simultaneous control over multiple physicochemical properties, such as crystal size, habit, chirality, poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 151 publications
0
31
0
Order By: Relevance
“…3 More recently, the surfactant-templating approach has also been extended to the synthesis of hierarchical zeolites in which the surfactant can be used to generate intracrystalline mesoporosity in the structure of these microporous materials. 4 Among the different procedures developed to generate secondary porosity within zeolites, [5][6][7][8][9][10] surfactant-templating in alkaline media allows for the incorporation of mesoporosity with tailored dimensions, while simultaneously maintaining the strong acidity and hydrothermal stability of the original zeolite. [11][12][13][14][15] The structure of surfactant-templated zeolites has been resolved by a combination of advanced gas adsorption, rotation electron diffraction (RED), and electron tomography (ET), which unambiguously confirmed the presence of intracrystalline mesoporosity within the zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…3 More recently, the surfactant-templating approach has also been extended to the synthesis of hierarchical zeolites in which the surfactant can be used to generate intracrystalline mesoporosity in the structure of these microporous materials. 4 Among the different procedures developed to generate secondary porosity within zeolites, [5][6][7][8][9][10] surfactant-templating in alkaline media allows for the incorporation of mesoporosity with tailored dimensions, while simultaneously maintaining the strong acidity and hydrothermal stability of the original zeolite. [11][12][13][14][15] The structure of surfactant-templated zeolites has been resolved by a combination of advanced gas adsorption, rotation electron diffraction (RED), and electron tomography (ET), which unambiguously confirmed the presence of intracrystalline mesoporosity within the zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of zeolite growth modifiers, Lupulescu and Rimer first reported in 2012 the use of ZGMs, such as functional organic molecules found in silica proteins, termed silicateins or silaffins, to alter the anisotropic rate of step growth on the surface of crystals, thereby regulating the morphology of the synthesized silicalite‐1 zeolite . Zeolite growth modifiers can be added to the crystallization medium in small amounts without significantly altering the growth environment, while they can be designed to have specific binding to a particular crystal surfaces to enhance exposure of the desired crystallographic faces . Various zeolite growth modifiers, including alcohols, amines, organophosphine oxides, crown compounds, cationic polymers, and peptoids have achieved a high degree of control over zeolite crystal morphology for silicalite‐1, ZSM‐5, zeolite L, SSZ‐13, and ZSM‐22 beyond what is attainable in the absence of ZGMs.…”
Section: Roles Of Organic Small Moleculesmentioning
confidence: 99%
“…[21] Zeolite growth modifiers can be added to the crystallization medium in small amounts without significantly altering the growth environment, while they can be designed to have specific binding to a particular crystal surfaces to enhance exposure of the desired crystallographic faces. [2] Various zeolite growth modifiers, including alcohols, amines, organophosphine oxides, crown compounds, cationic polymers, and peptoids have achieved a high degree of control over zeolite crystal morphology for silicalite-1, [21] ZSM-5, [24] zeolite L, [25] SSZ-13, [26] and ZSM-22 [27] beyond what is attainable in the absence of ZGMs. Some zeotype molecular sieves have been tuned with ZGM, such as the modification of silicoaluminophosphate SAPO-35 mophology through the addition of glucosamine.…”
Section: Zeolite Growth Modifiermentioning
confidence: 99%
See 2 more Smart Citations